How environment selects: Resilience and survival of microbial mat community within intermittent karst spring Krčić (Croatia). Issue 2 (15th January 2019) - Kolda, Anamarija; Petrić, Ines; Mucko, Maja; Gottstein, Sanja; Žutinić, Petar; Goreta, Gordana; Ternjej, Ivančica; Rubinić, Josip; Radišić, Maja; Udovič, Marija Gligora
Abstract: We conducted an on‐site monitoring study involving seasonal collection of microbial mats samples from the Krčić spring located in the Dinaric karst in Croatia. This intermittent karst spring is characterized by oligotrophic conditions and extreme water regime fluctuations. Extreme conditions at the Krčić included summer drought followed by strong rains in the autumn as well as freezing ambient temperature during winter. By using two phylogenetic markers, 16S rRNA (total Bacteria) and internal transcribed spacer (ITS) region (Cyanobacteria), we aimed to detect the impact of intense seasonal fluctuations of environmental parameters in shaping (and/or selecting) the microbial mat community of the Krčić spring. Microbial mat community was found to harbour bacteria belonging to 11 different phyla with Cyanobacteria making the community core (>50%), followed by Alphaproteobacteria. The most abundant cyanobacterial genera included Microcoleus, Phormidium, and uncultured Antarctic cyanobacterium. In two mat samples, collected during conditions of low temperatures and strong bora wind (winter 2014) and during drought period (summer 2015), Cyanobacteria were diminished within the community. Under the extreme cold populations found to proliferate included Planctomycetes and candidate phylum TM6, found specifically in this sample. Members of the phyla Firmicutes were strictly found during the drought summer period followed by Cytophagia‐Fibrella, Polymorphobacter, Polaromonas, and Massilia . During the event of high water inflow following the drought, Cyanobacteria represented 90% of the community in which specific desiccant‐tolerant Chroococcidiopsis, Calothrix, and Pleurocapsa species appeared having mechanisms for quick recolonization of environments.